Research on Solid Propellant Wet-Heat Aging Mechanism and Aging Test Characterization Methods - Wang, Ximing; Miao, Heyang; Li, Jinhang (International Journal of Materials Science and Technology Studies, 2025)
Solid propellants are critical in aerospace and military applications. HTPB solid propellants are widely used because of their excellent performance, but hot and humid environments have a significant impact on their performance. This paper reviews the research progress of HTPB solid propellant wet heat aging mechanism and aging performance test characterization method. With respect to the moisture-heat aging mechanism, chemical aging is manifested by polymer chain breakage and reorganization, and physical aging is manifested by the migration of plasticizers leading to microstructural instability; In the aging test characterization method, there are macro test and fine test. The current study suffers from homogenization of method application, little qualitative analysis, incomplete exploration of aging mechanisms and poor accuracy of life prediction models. In the future, new anti-aging additives should be developed and combined with artificial intelligence to optimize the aging prediction model.